Teachers’ First Language Use in Second Language Learning Classroom Context: A Questionnaire-based Study - Hassan Mohebbi; Sayyed Mohammad Alavi (Bellaterra Journal of Teaching & Learning Language & Literature, 2014)
Recently the issue of having recourse to second language (L2) learners’ first language (L1) in second language acquisition (SLA) is receiving a great amount of attention in SLA research. There has been a great deal of claims and counter-claims with respect to L1 use in L2 learning. The findings of L2 research to date cast doubt on the rationales of proponents of exclusive use of L2.  Researchers and practitioners who have observed L2 classrooms have identified different functions of L1 in L2 learning. Drawing on previous research as a framework, the present study investigates teachers’ beliefs and perceptions about L1 use in English-as-a-foreign language (EFL) learning contexts. To this end, seventy-two L2 teachers volunteered to fill in a questionnaire which probed into their beliefs and perceptions about employing learners’ L1 (Persian) in L2 (English) learning. The data obtained revealed that the L2 teachers used L1 mainly to provide feedback, teach new vocabulary, explain grammar, build rapport, manage the class, give individual help to learners, and save time in lengthy task explanations. However, in contrast to the L2 studies to date in this field, the teachers expressed that they never fall back on learners’ L1 to explain instructions for assignments or projects. The findings might have significant implications for language teachers, in particular in EFL contexts, regarding the facilitative effects of L1 use on L2 learning. The pedagogical implications of the study are explained in detail.